A Synopsis of Corruption in Nigeria’s Fourth Republic - Benjamin Terzungwe Tough; Esther Anenge Gbaden (International Studies Journal)
Corruption permeates all aspects of human engagements. No society however civilized can claim to be devoid of the phenomenon of corruption. However, on comparative basis, developing societies of the world such as those in Asia and Africa seem to be worse hit. One of such societies battling with the menace of corruption is Nigeria. The paper therefore, sets out to explore the evolution, causes and incidence of corruption as well as its effects with a view to suggesting a way out of the quagmire. To achieve this, the paper utilized content analysis of data accessed from secondary sources to historicize and lay the causes of corruption especially as they relate to the peculiar nature of Nigeria. The paper contextualized the incidences of high profile corruption in the country especially in the fourth republic and the effects of such ruthless actions, activities and inactionand what they portend for Nigeria in her modest efforts to democratize its polity. The paper concludes that Nigeria’s prosperity has been greatly hampered by extraordinary and massive corruption in the land so that there is a huge deficit in national progress, development and welfare of the citizens. The way forward is to strengthen anti-corruption institutions towards prevention and punishment of corrupt activities as well as ensure good governance in Nigeria